Body composition characteristics predict sexual functioning in obese women with or without PCOS. - Zueff, Lucimara Nobre; Lara, Lúcia Alves da Silva; Vieira, Carolina Sales; Martins, Wellington de Paula; Ferriani, Rui Alberto (Journal of Sex & Marital Therapy)
Polycystic ovary syndrome is frequently related to obesity and hyperandrogenism that potentially may impair sexual function. This case-control study aimed to determine the effect of the polycystic ovary syndrome on the sexual functioning of obese women and to determine which body measures can predict sexual functioning among 87 sexually active women obese women with and without polycystic ovary syndrome, 18-40 years old, divided in two groups; obese women (n = 44) or obese women with polycystic ovary syndrome (n = 43). The groups were compared using the Sexual Quotient-Female version and Hospital Anxiety and Depression scales, and by serum tests. No significant difference between groups was observed in weight, waist-hip ratio, body mass index, serum glucose, cholesterol, triglycerides, total testosterone, sex hormone binding globulin, total Sexual Quotient-Female version score, and the total score of ≤ 60 for subjects (risk for sexual dysfunction) and Hospital Anxiety and Depression. Significant difference was observed in age, parity, and Free Androgen Index. Each unit increase in waist-hip ratio conferred a greater chance of score of ≤ 60. A height of less than 161 cm and the presence of depression were found to be risk factors with a score of ≤ 60. Women with a score of ≤ 60 had significantly smaller hip measurements and waist-hip ratio. The presence of polycystic ovary syndrome was not a risk factor for decreased sexual functioning.